Teo- y narco-logías: Los mercaderes del templo en El narco negocia con Dios de Sabina Berman - Meléndez, Priscilla (Latin American Theatre Review, 2018)
The concern with ethics and the search for goodness in Mexican dramatist Sabina Berman’s play El narco negocia con Dios (2012) arise from the moral chaos of contemporary Mexico, suffocated by narco culture, the collapse of its judiciary, and rampant corruption. Responding to questions about morality and which actions are considered good or bad, El narco places spectators within a shifting and cartoonish moral landscape in which the inconsistencies of blatant evil and sanctimonious goodness are parodied, leading the audience to confront liminal ideas of morality that exceed the usual binaries of social and ethical thought. This play’s theatrical inventiveness lies in its exploration of two issues with a lengthy philosophical history: religion’s role in morality and chronological time’s role in human existence. In terms of the former, Berman’s play parodies biblical discourse, beginning with its title. As for the latter, the play features frequent plot breaks that go against the conventions of irreversible, linear time. El narco ultimately rejects a religious vision of morality that is frequently binary and paternalistic, proposing a more complex, pluralistic vision that critiques human sociopolitical and cultural conduct from a secular standpoint, even as it questions the Western concept of linear, progressive time.